2018
DOI: 10.1093/hmg/ddy108
|View full text |Cite
|
Sign up to set email alerts
|

The antidepressant tianeptine reverts synaptic AMPA receptor defects caused by deficiency of CDKL5

Abstract: Mutations in the X-linked cyclin-dependent kinase-like 5 (CDKL5) gene cause a complex neurological disorder, characterized by infantile seizures, impairment of cognitive and motor skills and autistic features. Loss of Cdkl5 in mice affects dendritic spine maturation and dynamics but the underlying molecular mechanisms are still far from fully understood. Here we show that Cdkl5 deficiency in primary hippocampal neurons leads to deranged expression of the alpha-amino-3-hydroxy-5-methyl-4-iso-xazole propionic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 53 publications
5
27
0
1
Order By: Relevance
“…Input resistance was not altered between R59X mice and WT littermates (data not shown), suggesting that cell size does not vary significantly between genotypes. Together, these electrophysiological data demonstrate a physiologically relevant increase in synaptic GluA2-lacking AMPARs in R59X mice, consistent with the immunohistochemical results and results from published cell culture studies (Tramarin et al, 2018).…”
Section: Elevated Early-phase Ltpsupporting
confidence: 90%
See 2 more Smart Citations
“…Input resistance was not altered between R59X mice and WT littermates (data not shown), suggesting that cell size does not vary significantly between genotypes. Together, these electrophysiological data demonstrate a physiologically relevant increase in synaptic GluA2-lacking AMPARs in R59X mice, consistent with the immunohistochemical results and results from published cell culture studies (Tramarin et al, 2018).…”
Section: Elevated Early-phase Ltpsupporting
confidence: 90%
“…Given that previous studies support a role for CDKL5 in stabilizing excitatory synapses (Ricciardi et al, 2012;Della Sala et al, 2016) and that dysregulated GluA2 has been observed in an in vitro model of CDD (Tramarin et al, 2018), we hypothesized that R59X mice may have molecular and functional alterations in AMPAR subunits associated with the aforementioned behavioral deficits and seizure susceptibility. To investigate whether R59X mice show AMPAR subunit dysregulation, we performed western blot analysis in cortical and hippocampal tissue of membrane-bound AMPAR subunits GluA1 and GluA2, the predominant AMPAR subunits in the brain (Lu et al, 2009; Reimers Figure 3.…”
Section: Decreased Membrane-bound Glua2:glua1 Protein In R59x Hippocamentioning
confidence: 89%
See 1 more Smart Citation
“…Studies have been conducted to develop precise therapy based on the biological, metabolic and genetic basis of CDD. These studies include the use of NMDA (N-methyl-D-aspartate) receptor modulators [50]; allopregnanolone (a neurosteroid that restores normal microtubule morphology) [51,52]; tianeptine, which is an antidepressant affecting AMPA (α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid) receptors [53]; or insulin-like growth factor IGF-1 activating the Akt/mTOR pathway [54]. Hopes are related to gene therapy as a causal treatment for disorders due to CDKL5 mutations.…”
Section: Therapymentioning
confidence: 99%
“…For example, abnormal accumulation of GluN2B and SAP102 were observed in hippocampus of CDKL5 knockout mice (Okuda et al, 2017). The expression and surface insertion of alpha-amino-3hydroxy-5-methyl-4-iso-xazole propionic acid receptors (AMPAR) was decreased by CDKL5 deficiency (Tramarin et al, 2018). Thus, CDKL5 exerts important function in maintaining mature synapse and loss of CDKL5 in mature neurons may contribute to the pathology of CDKL5 disorder.…”
Section: Role Of Cdkl5 In Maintaining Synaptic Functionmentioning
confidence: 99%